A Character Education Learning Model Grounded in Sundanese Cultural Philosophy: An Analysis of Dedi Mulyadi’s Public Leadership - Yatun Romdonah Awaliah; Sutrisna Wibawa; Rony Kurniawan Pratama (Jurnal Pendidikan Progresif, 2026)
Character education in Indonesia, despite its codification in the Penguatan Pendidikan Karakter framework and the Profil Pelajar Pancasila project, continues to rely on normative content that remains distant from students’ cultural and digital lives, even as digital communication has become a primary site where values are displayed, contested, and absorbed. This study develops a five-stage conceptual framework for character education grounded in Sundanese cultural philosophy, reading the public communication of West Java Governor Dedi Mulyadi as a contemporary site of cultural pedagogy. Dedi Mulyadi is chosen as the focal figure not because his political program is endorsed, but because the tension between authentic cultural performance and strategic image-making that his account exemplifies is precisely where students’ ethical formation in the digital age is most actively tested. a qualitative design combining Fairclough’s three-dimensional Critical Discourse Analysis with multimodal reading was applied to a purposive corpus of eighteen Instagram posts from the @dedimulyadi71 account, selected from a shortlist of forty-two posts through pre-specified inclusion criteria and supplemented by verified news reports. Inter-coder agreement was assessed at the level of value-cluster assignment, with an initial Krippendorff’s alpha of 0.74, which reached full consensus after structured deliberation. the analysis identifies five recurrent value clusters, namely handap asor, someah hade ka semah, silih asah, silih asih, and silih asuh, which surface through egalitarian dialogue, the Sundanese loma register, affective gestures, and embodied performances that function as symbolic capital. These clusters are operationalized into a cyclical conceptual framework with five stages: exploration, identification, reflection, internalization, and contextual application, with a deliberate critical-reflection stage that guards the framework against uncritical admiration of populist style. Conclusion: Sundanese cultural philosophy can be transformed into a contextual, humanistic, and critically aware framework for character education when digital leadership content is treated as pedagogical material for analysis rather than admiration. Keywords: character education, Sundanese cultural philosophy, critical discourse analysis, ethnopedagogy, digital leadership.